Analisis SWOT pada Usaha Kuliner Soto Kadipiro & Ingkung Pengasih Yogyakarta: Penelitian - Yuli Astuti; Aurelia Liony Aviacella (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The rapid development of the culinary industry in Indonesia has created fierce competition, including in the Yogyakarta culinary market. Soto Kadipiro & Ingkung Pengasih, as one of the legendary culinary businesses, faces challenges to maintain and improve its position in the market. the strategic location near the airport provides great opportunities, although tight competition and distance from the city center are threats that need to be overcome. Strategic recommendations include improvements in service speed, increased cleanliness, development of more aggressive marketing strategies, menu innovation, and efficient cost management.